Detecting conflictive cultural factors in complex scenarios of intervention: Military and local actors in interaction - Durán, Marién; Avalos, Antonio (UNISCI Journal, 2016)
The integration of cultural elements into the operational planning process is a complex task that requires practical and theroretical tools for a wide comprehension of the context to help solve the problem. This article shows the results of an empirical research which presents conflicting cultural factors as the starting point for the construction of mediating structures. The main result of our research is a partial cognitive structure, a system of ideas, represented in a template listing the basic conflictive factors at the tactical level that military could find in the development of their tasks. The template is also a valuable aid to design military training curricula and to be applied to any post-conflict stability operation in complex environments resulting from irregular or asymmetric conflicts.
Keywords: military forces; cultural competence; conflicting cultural factors; peacekeeping; local actors; post-conflict stability operations